The Experiences of Male Nursing Students at North-West University: Insights from Mafikeng Campus - Mohulatsi, Makgake Ziphorah; Garutsa, Tendayi Clotilda; Motswaledi, Thabang Richard (Journal of Ecohumanism, 2024)
Men in nursing are still seen as unusual for being in a profession that the society perceives as suitable only for females. There is also the notion that men have difficulty caring, traditionally, men are resilient and often are told "men do not cry", they are not supposed to show emotion, if they do, they tend to be considered weak. Men who choose nursing as a career not only risk challenging gender-based stereotypes but gender roles defined traditionally as well. The purpose of this paper was to explore the experiences of male nursing students at NWU (MC) and the empirical evidence suggests that there is still much to be done in institutions of higher learning to enable male nursing students to also feel a sense of belonging in their respective nursing programs. The study utilized qualitative research method in exploring the issues of gender with a particular focus on masculinity and it has uncovered the concept of hegemonic masculinity. Structured interviews were employed, and the data was transcribed and analysed through content analysis. A comprehensive search of the literature from different disciplines reveals deeper issues than just the commonly held assumption that nursing is not masculine. The findings of the study suggest that Connell’s theory of masculinity should not attempt to balance supposedly masculine and feminine qualities, but to challenge the assumption that masculinities are predominantly masculine or feminine. Recommendations include institutions creating campaigns that will ensure that only students that are passionate about nursing are recruited and implement strategies that will improve the experiences of male nursing students in institutions of higher learning.